Tuvalu : 2018 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2018)
Tuvalu is a fragile micro state. The country's remoteness, narrow production base, and weak banking sector constrain private sector activity, leaving public expenditure as the main source of growth. The DSA finds that Tuvalu remains at high risk of debt distress.